Farmers Adoption of Organic Rice Production in Chachoengsao Province, Thailand - Suneeporn Suwanmaneepong; Chanhathai Kerdsriserm; Krichanont Iyapunya; Unggoon Wongtragoon (My University, 2020)
This study analysed the factors affecting the adoption of organic rice production in Chachoengsao Province, Thailand. Primary data were collected through structured questionnaire completed by 108 farmers: (58 organic rice farmers and 50 non-organic rice farmers) in Chachoengsao Province, Thailand. A t-test was employed to investigate the differences in the demographics of organic and non-organic rice farmers, and percentage mean, and standard deviation was used to describe farmers’ attitudes. Logistic regression was employed to investigate factors influencing organic rice adoption, educational level, and farm size were significantly different between the organic and non-organic rice farmers. Education (positive), farming experience (positive), age of household head (negative) and farm size (negative) had highly significant (p ≤ 0.01) influences on organic farming adoption. The farmers’ attitude toward environmental concern was the most important reason for adopting organic rice farming. This research identified the factors affecting the adoption of organic rice farming; this information can be used to encourage farmers to practice organic rice farming in the targeted organic rice area in Thailand. In addition, the farmers’ attitudes toward organic farming systems could be used to help support farmers practicing organic rice farming.
Keywords: organic rice adoption, organic rice production, organic farming adoption, farmer attitudes.
Keywords: Rice farming; Demographics; Organic production; Organic Food and Agriculture